Effects of malnutrition on mortality in oldest-old inpatients with COVID-19 in the GERIA-COVID cohort. (July 2022) - Sanchez-Rodriguez, Dolores; Sacco, Guillaume; Gautier, Jennifer; Brière, Olivier; Annweiler, Cédric; ,
Highlights: We assessed the impact of malnutrition on mortality risk in inpatients aged 80 years or more with COVID-19 in the hospital-based GERIA-COVID cohort. Malnutrition was assessed using the geriatric nutritional risk index (GNRI). Malnutrition according to the GNRI was not associated with mortality within the first 3 months of diagnosis of COVID-19. Abstract: We assessed the impact of malnutrition on 14-day, 28-day, and 3-month mortality risk in oldest-old inpatients aged ≥80 years with COVID-19 in the hospital-based GERIA-COVID cohort. Malnutrition was assessed on hospital admission using the Geriatric Nutritional Risk Index (GNRI). Potential confounders were age, sex, functional abilities, number of acute health issues, CRP level, hypertension, cardiomyopathy, malignancies, use of antibiotics, and respiratory treatments. Seventy-eight participants (88.9 ± 4.3 years old, 55% women) were included. Of these, 82.1% had survived at day 14, 78.2% at day 28, and 70.5% after 3 months. No association between malnutrition according to the GNRI and 14-day ( P  = 0.324), 28-day ( P  = 0.166), or 3-month mortality ( P  = 0.109) was found. Thus, malnutrition according to the GNRI was not associated with mortality within the first 3 months of diagnosis of COVID-19 among oldest-old inpatients.